DETERMINED OF OFFICE FACILITIES AND WORK DISCIPLINE ON EMPLOYEES PERFORMANCE OF DEVELOPMENT PLANNING REGIONAL DISTRICT OF BATU BARA - Novia Ruth Silaen (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Darma Agung (LPPM_UDA), 2018)
The purpose of this study was to determine the effect of office facilities and work discipline on the performance of employees of the Batu Bara Regional Development Planning Agency, with the object of research limited to office facilities and work discipline as independent variables and performance as dependent variables. The sample in this study is 30 respondents. The method used in this study is quantitative analysis with multiple linear regression methods. The result of the regression equation is Y = -0.745 + 0.854X1 + 0.128X2, meaning the constant value is -0.745, which if the company has decreased, it will affect the performance of -0.745, and the unstandardized coefficients value in the office facility model (X1) is equal to 0.854, and in the work discipline model (X2) has a value of 0.128, which means that if one unit increases in the independent variable, it will experience an increase in the dependent variable. T-test analysis of office facilities variable has a t-count greater than t-table (7,715 > 2,0484), it can be concluded that the office facility variable (X1) has a significant effect on the performance variable (Y), and for the work discipline variable t-count is smaller than t-table (0.775 < 2.0484), it can be concluded that the working discipline variable (X1) has no significant effect on the performance variable (Y). F-test analysis of office facility variables (X1) and work discipline (X2) on performance (Y) F-count is greater than F-table (83,334 > 3,34), it can be concluded that the influence of independent variables simultaneously (simultaneously) on variables bound, and based on the testing of Determination Adjusted R-Square (R2) variable of office facilities (X1) and work discipline (X2) shows a value of (0.850), where the value approaches 1, which means that the independent variables provide almost all the information needed for predict the variation of the dependent variable.